Bovine genome. Mapping and trypanotolerance. Proceedings of a workshop - Teale, A.J. (1991)
Presents reports of the gene mapping laboratories and of those laboratories and groups concerned directly with trypanotolerance research and summarises the final round table discussion, and the workshop's recommendations concerning genome mapping development and the production and use of trypanotolerance resource material.